Non-audit service fees and audit quality: The impact of auditor specialization - LIM, Chee Yeow (Institutional Knowledge at Singapore Management University, 2008)
We posit that the effect of non-audit fees on audit quality is conditional on auditor industry specialization. Industry specialist auditors are more likely than nonspecialists to be concerned about reputation losses and litigation exposure, and to benefit from knowledge spillovers from the provision of non-audit services. We find evidence that audit quality measured by increased propensity to issue going-concern opinion, increased propensity to miss analysts' forecasts, as well as higher earnings-response coefficients increases with the level of non-audit services acquired from industry specialist auditors compared to nonspecialist auditors.